Transactions on rough sets XIV - Peters, James F.; Peters, James F (Lecture Notes in Computer Science, 2011)
The LNCS journal Transactions on Rough Sets is devoted to the entire spectrum of rough sets related issues, from logical and mathematical foundations, through all aspects of rough set theory and its applications, such as data mining, knowledge discovery, and intelligent information processing, to relations between rough sets and other approaches to uncertainty, vagueness, and incompleteness, such as fuzzy sets and theory of evidence. Volume XIV contains 11 revised extended papers from the 12th International Conference on Rough Sets, Fuzzy Sets, Data Mining and Granular Computing, RSFDGrC 2009, held in Delhi, India. The topics include various rough set generalizations in combination with formal concept analysis, lattice theory, fuzzy sets and belief functions, rough and fuzzy clustering techniques, as well as applications to gene selection, web page recommendation systems, facial recognition, and temporal pattern detection. in addition, this volume contains a regular article on rough multiset and its multiset topology.